PENGARUH PROFITABILITAS TERHADAP KINERJA KEUANGAN DI PT. SEMEN BATURAJA (PERSERO) TBK - Zagoto, Sonia Vestiani (Universitas Nias Raya, 2025)
This research aims to determine the effect of profitability on financial performance at PT. Semen Baturaja (Persero) Tbk. This type of research is quantitative research that is associative in nature. The data analysis used is multiple linear regression analysis. The research results show that profitability has an effect on financial performance. Furthermore, in this research, a multiple linear regression analysis equation was obtained, namely Y=0.52+0.343+0.318=1.2684. This shows that if the x value is 0 then the coefficient of financial performance is 0.52. The Net profit margin regression coefficient of 0.343 shows the relationship that for every increase in the net profit margin variable by 1 unit, the financial performance variable will increase by 0.343 units. The return on assets regression coefficient of 0.318 shows the relationship that for every increase in the return on assets variable by 1 unit, financial performance will increase by 0.318. With this influence, Net profit margin and return on assets show an influence.